Pemberdayaan Masyarakat Melalui Pelatihan Pemandu Wisata Guna Mengembangkan Potensi Wisata Di Desa Panglungan Kecamatan Wonosalam Kabupaten Jombang - Richul Munawaroh Sayidin; Pieter Adam Telaumbanua; Syadwina Daniar; Richul Munawaroh (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Community empowerment is an effort to provide strength or power for the community so that it gets out of the problems faced. Community empowerment in Panglungan Village is carried out by organizing tour guide training or tour guides to increase tourist visits in Panglungan Village. Panglungan Village is one of the villages in Wonosalam District that has great tourism potential but still needs to be developed. The empowerment process has several stages, namely location selection, socialization of community empowerment, community empowerment process, and community independence. This writing aims to find out how community empowerment in Panglungan Village through human resource development by conducting tour guide training. The method used is through literature study and focus group discussion (FGD). Community empowerment in Panglungan Village is in accordance with the existing stages of empowerment. With the empowerment of the community through this tour guide training, it is hoped that the community will have the knowledge to become tour guides so that in the future they can support the tourism there.